2018
DOI: 10.1556/018.69.2018.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Extractability of polyphenols from black currant, red currant and gooseberry and their antioxidant activity

Abstract: In this study, we analyzed extracts of Ribes (black currant, red currant and gooseberry) fruits obtained with methanol, methanol 50% and water. For each extract total polyphenol content, total flavonoid content and total anthocyanin content was assessed. The antioxidant activity of extracts was evaluated by 1,1-Diphenyl-2-picrylhydrazyl (DPPH) and 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) radical scavenging capacity and by the photo-chemiluminescence (PCL) method. Identification and quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
29
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 32 publications
6
29
0
5
Order By: Relevance
“…Total phenolic acids were found between 113.73 and 1,822 mg GAE • 100 g -1 FW in raspberries, between 48.9 and 690.2 mg GAE • 100 g -1 FW in blackberries and between 290 and 2,611 mg GAE • 100 g -1 FW in gooseberries (Proteggente et al, 2002;Wada and Ou, 2002;Wang and Lin, 2002;Pantelidis et al, 2007;Giovanelli et al, 2012). In other studies, antioxidant activity was found in line with the findings of the present study in fruits of raspberry, blackberry and gooseberry (Wang and Lin, 2002;Barros et al, 2010;Bobinaitė et al, 2012;Laczkó-Zöldi et al, 2018;Chanyotha et al, 2019). Researchers determined the values of anthocyanin in raspberry 15.1-608.24 mg • 100 g -1 FW), blackberry (35.1-230.74 mg 100 • g -1 FW) and gooseberry (1.3-152.2 mg • 100 g -1 ) among different amounts (Laleh et al, 2006;Buřičová et al, 2011;Narváez-Cuenca et al, 2014;Kostecka-Gugała et al, 2015).…”
Section: Resultssupporting
confidence: 92%
“…Total phenolic acids were found between 113.73 and 1,822 mg GAE • 100 g -1 FW in raspberries, between 48.9 and 690.2 mg GAE • 100 g -1 FW in blackberries and between 290 and 2,611 mg GAE • 100 g -1 FW in gooseberries (Proteggente et al, 2002;Wada and Ou, 2002;Wang and Lin, 2002;Pantelidis et al, 2007;Giovanelli et al, 2012). In other studies, antioxidant activity was found in line with the findings of the present study in fruits of raspberry, blackberry and gooseberry (Wang and Lin, 2002;Barros et al, 2010;Bobinaitė et al, 2012;Laczkó-Zöldi et al, 2018;Chanyotha et al, 2019). Researchers determined the values of anthocyanin in raspberry 15.1-608.24 mg • 100 g -1 FW), blackberry (35.1-230.74 mg 100 • g -1 FW) and gooseberry (1.3-152.2 mg • 100 g -1 ) among different amounts (Laleh et al, 2006;Buřičová et al, 2011;Narváez-Cuenca et al, 2014;Kostecka-Gugała et al, 2015).…”
Section: Resultssupporting
confidence: 92%
“…Ця культура починає плодоносити на 2-й рік, а повноцінний врожай отримують на 3-й рік після садіння. Потенційна врожайність її становить понад 12 т/га [3,4]. За сприятливих погодних умов вона плодоносить щорічно.…”
Section: вступunclassified
“…Проте тенденція впливу удобрення та мульчування прикущових смуг була подібною. У варіанті без добрив цей показник становив 0,65-0,70 м 3 . Застосування N60P90K90 збільшувала його на 20-30 %, позакореневого підживлення препаратом Ріверм 3 % -на 50-51 % залежно від утримання при кущових смуг.…”
Section: результати дослідженьunclassified
See 2 more Smart Citations